Household time allocation and modes of behavior: a theory of sorts - Daniela Del Boca; Christopher J. Flinn (Institute for the Study of Labor (IZA), 2005)
We develop a simple model of household time allocation decisions under strong functional form assumptions regarding preferences and household production technology. We argue that the specification is general when allowing for unrestrictive forms of population heterogeneity in the parameters characterizing these functions. Moreover, we argue that the model is not capable of distinguishing among elements of a class of behavioral rules, including Nash bargaining and Nash equilibrium, without restricting population heterogeneity in arbitrary ways. However, preferences over mates for any given set of male and female characteristics will be a function of the behavioral rules used in married households. Using data from the PSID on market hours and time spent in household production, we estimate the marginal distribution of male and female characteristics and our two alternative behavioral assumptions, and perform some formal and informal comparisons of the Nash bargaining and Nash equilibrium rules' ability to predict the marital sorts observed in the data. Given the simplicity of the model of household behavior and marriage market equilibrium, it is perhaps not surprising that neither model provides good predictions. Overall, the evidence is slightly more supportive of the hypothesis that households behave noncooperatively.
Keywords: D13; J12; J22; 330; bilateral matching; household time allocation; Nash bargaining